Anti‐inflammatory effects of low molecular weight heparin derivative in a rat model of carrageenan‐induced pleurisy - Ceccarelli, Matteo (J Cell Mol Med, 2009)
Low molecular weight heparin derivatives are characterized by low anti‐coagulant activity and marked anti‐inflammatory effects that allow for these molecules to be viewed as a new class of non‐steroidal anti‐inflammatory drugs (NSAIDs). We show here that K5NOSepiLMW, an O‐sulphated heparin‐like semi‐synthetic polymer of the D‐glucuronic acid–N‐acetyleparoson disaccharide unit with low molecular weight, has marked anti‐inflammatory effects in a rat model of acute inflammation, the carrageenan‐induced pleurisy, commonly used to test NSAID efficacy. A 30‐min. pre‐treatment with K5NOSepiLMW (0.1, 0.5 and 1 mg/kg b.wt., given intrapleurally) attenuated the recruitment of leucocytes in the lung tissue and the pleural exudate, inhibited the induction of inducible nitric oxide synthase and cyclooxygenase‐2 (COX‐2), thereby abating the generation of nitric oxide and pro‐inflammatory prostaglandins such as PgE(2) and PGF(1α), reduced the inflammation‐induced nitroxidative lung tissue injury, as shown by tissue thiobarbituric acid‐reactive substances and nitrotyrosine, and blunted the local generation of cytokines such as interleukin‐1β and tumour necrosis factor‐α. All these parameters were markedly increased by intrapleural carrageenan in the absence of any pre‐treatment. The anti‐inflammatory action of K5NOSepiLMW is specific, as judged by the lack of therapeutic effects of B4/110, a biologically inactive cognate polysaccharide, given in the place of the authentic molecule. Moreover, K5NOSepiLMW showed similar effects as celecoxib (1 mg/kg b.wt), a COX‐2 inhibitor and well‐known NSAID. This study provides further insight into the mechanisms underlying the beneficial effects of heparin derivatives in inflammation and identifies K5NOSepiLMW as a novel, promising anti‐inflammatory drug.